Faktor yang Berhubungan dengan Speech Delay pada Anak Prasekolah - Salwa Zafirah, Amanda; Yuliana, Fitri; Wahdah, Rabia; Kusvitasari, Hairiana (Pustaka Galeri Mandiri, 2026)
Speech ability is an important indicator in the development of preschool-aged children. Speech Delay can affect a child's cognitive, social, and emotional aspects if not addressed early. Parental factors, especially maternal factors, such as knowledge, attitudes, and stimulation are thought to play a role in the development of children's speech abilities. This study aims to determine the relationship between maternal knowledge, maternal attitudes, and maternal stimulation with the incidence of Speech Delay in preschool-aged children at the Children's Polyclinic of Ulin Banjarmasin Regional Hospital. This study used a quantitative design with a cross-sectional approach. The study sample consisted of 32 respondents selected using an accidental sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed univariately and bivariately using the Chi-Square test. The results showed that 65.6% of children experienced Speech Delay, which consisted of the categories of suspect, mental retardation, and communication disorders. Bivariate analysis showed a significant relationship between maternal attitudes (p = 0.010) and maternal stimulation (p = 0.029) and children's speech ability, while maternal knowledge showed no significant relationship (p = 0.464). It can be concluded that maternal attitudes and stimulation play an important role in preschoolers' speech ability. Knowledge alone is not sufficient to prevent Speech Delay without active parenting practices